Deteksi Dini Penyakit Gout Pada Lansia di Wilayah Kerja Puskesmas Kalibaru Bekasi - Ria Amelia (Universitas Lancang Kuning, 2021)
Gout caused by hyperuricemia is a condition of high of uric acid in the blood. The condition of hyperuricemia in elderly is related to metabolic syndrome which is caused by slow rate of the body's metabolism. This activity aims to determine a prevalence of hyperuricemia in elderly at four Posbindu as a working area of ​​Kalibaru Health Center. Type of research is cross sectional with a simple random sampling method. The activity was carried out in August 2019. The method to measurement of uric acid levels by the strip method. The Descriptive test results showed a modus of the elderly is at the age of 65 years and the oldest at the age of 89 years. The percentage of elderly people who experience hyperuricemia based on WHO 2013 criteria as many as 8.8% from a total of 68 elderly. The conclusion of this activity indicates that 90% of elderly in the working area of the Kalibaru Helath Center have normal of uric acid levels.